Identification of School Leadership Strategy In Supporting Students Learning From Home During Pandemics - Herlan Suherlan; Arnadi Arnadi; Fahrina Yustiasari Liriwati; Kafrawi Kafrawi; Abd. Syahid (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Identifying school leadership strategies to support students learning from home during the pandemic is the core objective of this study. To answer the problem above, we have reviewed dozens of publications interested in discussing educational disruption during the outbreaks where the effect of the disruption forces students to study from home with all the problems that arise. We get the data from an online search, and we study it with a phenomenological approach. We evaluate the data with a coding system to know what and how school leadership responds to the pandemic. Based on the data and the discussion, we found that many things must and have been done by the school that does not have to wait for the direction of policy superiors from the central state. The support provided is, for example, teachers and school boards assisting students and guiding how to prevent students and parents from panicking through the disrupted period of the pandemic. Schools do not force students with assignments and work, but teachers should encourage collaborative learning with parents while maintaining progress. Thus, we hope this study is helpful to many parties.